Traceability matrix as a supplementary aid in system test planning - Averilla, Karen (University of the Philippines Diliman, 2010)
In today's era of high technology where the shift from traditional style workmanship to a techno savvy work environment is the trend, more and more companies are being restructured with advance technology and IT services. Automation has become the primary means of doing business be it in technical or non-technical industries. This resulted to the flourishing industry of IT and software development. With software companies abounding, one has to maximize its competitive advantage to stay in the game. Each project should be well-managed to avoid overshooting on both cost and time estimations and ending up in poor quality. Planning is very important in the software development process. An efficient plan can save up organization's time, effort and money. System Test Planning is a critical and rigorous process in software development. It involves ensuring product quality while balancing the amount of effort to be spent in product testing. As such, processes involved in this phase must be performed meticulously to generate an efficient Test Plan. This study presents a knowledge management tool that serves as a supplementary aid in system test planning for PAM, a group under the AO organization of EPM company. The tool aims to help build an efficient test estimate of documentation effort as part of the system test plan. The project also endeavors to help in identifying the documentation tasks for faster task distribution. As an end result of using the tool, this project hopes to increase product quality by making sure all aspects of the product are tested in relation to the changes in the product requirements. The development of the tool is a product of the process improvement efforts upheld by the company. It operates on the principle that at the level of daily work of the organization, quality management tools help people learn. This learning allows improvements to be made. When learning is shared among the members of the organization, knowledge and productivity increase. This is the framework that guides the project - the interaction of quality management and knowledge management at the systems level and daily work of the organization. Although the project is a result of having been identified as an area of improvement, particularly a process improvement, time constraint limits the researcher to measure the actual time improvement contributed by the use of the tool. Usability of the tool can only be measured by initial user feedback after tool completion. Actual tool usage was not gauged. Through process gap analysis, the Requirements Traceability Matrix was identified as the tool that best addresses the needs mentioned. The RTM is a type of document map that traces the relationship of requirements to the test documents. It is developed using MS Excel and housed in the company's electronic document repository. The creation, review, approval and maintenance of the tool are subject to the document control procedure of the company. At the end of the project, usability is evaluated using a survey of intended users in form of questionnaires.